The Wife’s Act of Refusing to Have an Intimate Husband (Equity, Sociological and Health Study) - Amin Songgirin (Institut Agama Islam Negeri (IAIN) Curup, 2021)
This paper discusses the hadith cursing angels against wives who do not want to be invited to bed. In discussing it, the author uses an equality approach, a sociological and health perspective. The problem of the bed is an important problem in the household because such rituals are a form of obedience and fulfillment of the rights of both parties as well as a form of worship. Angels act against a wife who refuses the husband's invitation to bed, even when she is menstruating. On the other hand, the husband also sins if his wife asks to make out, but the husband refuses, even though the reason is busy doing worship. So on the matter of the bed, there must be equality between husband and wife, because in addition to the purpose of physic (zahir) goodness, it is far from that to build inner (bathin) pleasure, namely sakinah, mawaddah wa rahmah. In essence, marriage is worship, so it must be interpreted as jima' as a form of worship, not as coercion or oppression.